2018
DOI: 10.1007/s13280-018-1058-3
|View full text |Cite|
|
Sign up to set email alerts
|

Using measures of wellbeing for impact evaluation: Proof of concept developed with an Indigenous community undertaking land management programs in northern Australia

Abstract: Combining insights from literature on the Theory of Change, Impact Evaluation, and Wellbeing, we develop a novel approach to assessing impacts. Intended beneficiaries identify and rate factors that are important to their wellbeing, their satisfaction with those factors now, and before an intervention. Qualitative responses to questions about perceived changes and causes of change are linked to quantitative data to draw inferences about the existence and/or importance of impact(s). We use data from 67 Ewamian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Although investment in ILSMPs was initially designed to support improved conservation and environmental management by the increased involvement of Indigenous people, over time, it has been more frequently reported as being able to improve the wellbeing of Indigenous people [7], with growing evidence that ILSMPs generate co-benefits. "Co-benefits" are a diverse range of benefits that reach far and above those associated with the environment (e.g., health, pride, confidence, and capacity building), and can accrue to a wide and diverse range of stakeholders, including Indigenous people [3,8] and funding bodies [5]. However, impacts are not necessarily all positive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although investment in ILSMPs was initially designed to support improved conservation and environmental management by the increased involvement of Indigenous people, over time, it has been more frequently reported as being able to improve the wellbeing of Indigenous people [7], with growing evidence that ILSMPs generate co-benefits. "Co-benefits" are a diverse range of benefits that reach far and above those associated with the environment (e.g., health, pride, confidence, and capacity building), and can accrue to a wide and diverse range of stakeholders, including Indigenous people [3,8] and funding bodies [5]. However, impacts are not necessarily all positive.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the recently reported wellbeing impact evaluation (W-IE) approach [8] and interviewed 190 Indigenous Australians in four ILSMPs-engaged communities. We first set out to identify which aspects of wellbeing were perceived as important to interviewees (hereafter referred to as important factors) and to then learn more about their perceptions of the way in which ILSMPs had (or had not) impacted those important factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is in addition to other crucially important contributions ILSMPs make to Indigenous well‐being (Larson et al. ) and to the longer‐term impacts that associated knowledge transfers generate (another important topic for future research). ILSMPs also support ecosystem functions and are known to have significant positive impacts on a range of other social and cultural values (Social Ventures Australia, , ).…”
Section: Discussionmentioning
confidence: 88%
“…Much research highlights the significant, positive, contribution that Indigenous Land and Sea Management Programs (ILSMPs) make to Indigenous income and employment outcomes and well‐being (Social Ventures Australia , ; Barber & Jackson ; Larson et al. ). Here, we seek to contribute to the small but growing literature focused on assessing the multiple outcomes from ILSMPs, learning more about the regional economic impact of (mostly government) ILSMP expenditure and the distribution of the resulting economic gains between Indigenous and non‐Indigenous people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation